PELAKSANAAN DAN PERAN ADMINISTRASI DESA DALAM PEMBANGUNAN DESA MELALUI PERANGKAT DIGITAL (Jurnal Pengabdian Masyarakat UNAMA, 2023)
Indonesia used decentralization in managing every region in the country. Every region or city can manage its own government but still with the nation's goals and purpose. The decentralization system is a delegation of authority and responsibility or power to carry out part or all the management and administrative functions of government from the central government to regions or institutions that are extensions of the central government. The city/regency consists of sub-districts, each sub-district led by a head for sub-districts. As for the village area, it will be led by a village head. The community service will hold in Sungai Bahar Unit 9, Tanjung Harapan Village, Bahar Tengah District, Muaro Jambi Regency, Jambi Province. Tanjung Harapan Village is one of the villages with most people working as palm oil farmers and laborers. People in Sungai Bahar especially Tanjung Harapan Village cannot use technology or digital tools to carry out village activities and the role of village administration. Therefore, with these Community Services, it is hoped that the community and village officials can maximize the available digital technology.